Prediction of In Vivo Atenolol Removal by High-Permeability Hemodialysis Based on an In Vitro Model - Kahina Daheb; Jean-Philippe Lecours; Mark L. Lipman; Patrice Hildgen; Julie J. Roy (Frontiers Media S.A., 2013)
Purpose. In order to update our data on drug dialyzability using the high-permeability dialysis membranes, atenolol elimination by an in vitro dialysis model was compared to that observed in six patients during high-permeability hemodialysis (HD), and the predictive value of the model was evaluated. Methods. Atenolol clearance was evaluated in six patients undergoing chronic HD. They were considered as eligible candidates if they were between 18 and 80 years of age, had a body mass index between 19 and 30 kg/m2, underwent HD and were taking atenolol on a regular basis in oral tablet form for at least 1 month before the study started. Atenolol clearance was also evaluated in three in vitro dialysis sessions with high-permeability polysulfone membrane. Atenolol was dissolved in 6 L of Krebs-Henseleit buffer with bovine serum albumin. Dialysis parameters were set to mirror as much as possible the patients' parameters (flow rate: 300 mL/min, dialyzate flow: 500 mL/min). After sample collection, drug concentrations were measured with high performance liquid chromatography. The comparison between in vivo and in vitro atenolol elimination kinetics was performed by drawing the curve fittings of concentrations vs. time on SigmaPlot 12, and adding a 95% prediction interval to each elimination curve fitting. Results. Mean dialysis clearance of atenolol in vitro and in vivo was 198 ± 4 and 235 ± 53 mL/min, respectively. Atenolol was significantly removed within the study time period in both in vitro and in vivo experiments. By the end of in vitro dialysis, atenolol remaining in the drug reservoir was less than 2% of initial arterial concentration. Conclusion. Our study has indicated that atenolol is almost entirely cleared during high-permeability hemodialysis. Furthermore, the in vitro prediction interval of the drug elimination curve fitting could forecast its in vivo elimination especially at the end of dialysis.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.